2014
DOI: 10.1038/ejcn.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugars in solutions on subjective appetite and short-term food intake in 9- to 14-year-old normal weight boys

Abstract: Change from baseline subjective average appetite was the highest after sucrose, but only the glucose solution suppressed FI at the test meal 60 min later in NW boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
(70 reference statements)
1
23
0
Order By: Relevance
“…Total dietary fructose has been shown to be positively related to increased visceral adiposity, increased blood pressure, and HOMA-IR in a large sample of adolescents (Pollock et al, 2012). An experiment comparing glucose, HFCS, sucrose, and sucralose found that food intake after a HFCS or sucrose drink led to higher energy intake at a subsequent ad libitum meal (Van Engelen et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total dietary fructose has been shown to be positively related to increased visceral adiposity, increased blood pressure, and HOMA-IR in a large sample of adolescents (Pollock et al, 2012). An experiment comparing glucose, HFCS, sucrose, and sucralose found that food intake after a HFCS or sucrose drink led to higher energy intake at a subsequent ad libitum meal (Van Engelen et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on the satiating action of acute intake of either fiber or SSB (Chang et al, 2012; Soenen & Westerterp-Plantenga, 2007; Van Engelen et al, 2014b; A J Wanders et al, 2011; Anne J Wanders et al, 2013). Research has shown acute satiety after a sugar pre-load (Anderson & Woodend, 2003), however the effect of prolonged sugar consumption is, to date, understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Those dieting, taking medications affecting brain physiology, breakfast skippers, or with learning, behavioral, or emotional difficulties were excluded from the study. Participant characteristics are described in greater detail in our previous publication (11). The study was approved by the Research Ethics Board, Mount Saint Vincent University.…”
Section: Participantsmentioning
confidence: 99%
“…The subjective appetite and food intake data were previously reported (11). Following a telephone screening interview with the parent, an in-person interview was scheduled where informed written consent and assent were obtained from the parent and child, respectively.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation